Thermosensitive, Stretchable, and Piezoelectric Substrate for Generation of Myogenic Cell Sheet Fragments from Human Mesenchymal Stem Cells for Skeletal Muscle Regeneration. (9th November 2017) - Yoon, Jeong‐Kee; Misra, Mirnmoy; Yu, Seung Jung; Kim, Han Young; Bhang, Suk Ho; Song, Seuk Young; Lee, Ju‐Ro; Ryu, Seungmi; Choo, Yeon Woong; Jeong, Gun‐Jae; Kwon, Sung Pil; Im, Sung Gap; et al.
Abstract: In a native muscle microenvironment, electrical and mechanical stimuli exist in the form of action potentials and muscle contraction. Here, a cell culture system is developed that can mimic the in vivo microenvironment and provide these stimuli to cultured cells, and it is tested whether the stimulation can promote myogenic differentiation of human umbilical cord blood mesenchymal stem cells (hUCBMSCs). A thermosensitive, stretchable, and piezoelectric substrate (TSPS) is fabricated by polydimethylsiloxane spin‐coating of aligned ZnO nanorods and subsequent poly( N ‐isopropylacrylamide) grafting on the polydimethylsiloxane surface. Pulsatile mechanoelectrical cues are provided to hUCBMSCs cultured on the TSPS by subjecting the TSPS to cyclic stretching and bending, resulting in significant promotion of myogenic differentiation of hUCBMSCs as well as intracellular signaling related to the differentiation. After differentiation ex vivo, the cells are detached from the TSPS in the form of cell sheet fragments. Injection of the cell sheet fragments of differentiated cells into injured mouse skeletal muscle shows improved cell retention and muscle regeneration as compared to injection of either undifferentiated cells or differentiated dissociated cells. This system may serve as a tool for research on the electrical and mechanical regulation of stem cells and may be used to potentiate stem cell therapies. Abstract : Thermosensitive, stretchable, and piezoelectric substrates can mimic the skeletal muscle microenvironment by providing pulsatile mechanoelectric cues to human umbilical cord blood mesenchymal stem cells (hUCBMSCs). Electrical and mechanical stimulations induce skeletal muscle differentiation of hUCBMSCs, and the differentiated cell sheet fragments are a good source of cell therapy to treat skeletal muscle diseases.